Surgical ligation of patent ductus arteriosus in dogs: Incidence and risk factors for rupture. Issue 4 (16th March 2022) - Grimes, Janet A.; Thieman Mankin, Kelley M.
Abstract: Objective: To determine the rates of rupture and mortality associated with surgical ligation of patent ductus arteriosus (PDA) in dogs and to identify risk factors for rupture. Study design: Retrospective cohort. Animals: Two‐hundred and eighty‐five dogs with PDA undergoing surgical ligation. Methods: Information regarding signalment, weight, surgical findings, complications, presence of residual flow, and survival was recorded. Age, weight, and presence of residual flow were compared between cases with and without rupture. Results: The initial surgical approach was extrapericardial (144), intrapericardial (46), not reported (94), or Jackson‐Henderson (1). Rupture of the PDA occurred in 7.0% of dogs (20/285, 13 extrapericardial, 3 intrapericardial, 4 not reported). No difference in age or weight was found between dogs with and without rupture. Overall mortality was 0.4% (1/285). Additional major complications occurred in 1.4% of dogs, all in the nonrupture group. The overall rate of residual flow after ligation was 9.4%. Dogs with rupture were more likely to have residual flow than those without rupture ( P  = .012). If ligation was performed after rupture (rather than hemostasis only), no difference in residual flow rates ( P  = .398) was noted between dogs with rupture and those without. Conclusion: The rate of rupture with surgical ligation of PDAs was low. No specific risk factors for rupture were identified. Clinical significance: Successful treatment of PDA rupture is possible, evidenced by the low mortality rate in this population of dogs. Ligation of the PDA after rupture, either in the concurrent or a subsequent procedure, reduces the odds of residual flow.